Wake up, color pup - Morley, Taia (Random House Children's Books, 2019)
A bright yellow bird promises to bring adventure to sleepy Pup's gray world. As Pup follows his new friend on a walk, each discovery ignites a new feeling and corresponding color, until Pup is saturated with them. But when a storm comes, Pup's color is drained as fear sweeps through him. Only his curious yellow friend remains bright, and encourages him to keep his chin up, play, and carry on!